Penggunaan media gambar dalam sosialisasi sekolah tatap muka kepada anak sekolah dasar selama masa pandemi covid – 19 - Siti rohmawati; Syarufah Syarufah; Krisna Suda Pratama; Liswanti Liswanti; Muhammad Said Agil Lestianto; Afriyadi Sofyan (Indonesian Institute For Counseling, Education and Therapy, 2021)
Indonesia has been affected by the Covid-19 pandemic in the education sector. The government has suspended learning activities in both formal and non-formal schools to suppress the spread of Covid-19. Based on data from the Covid-19 Task Force, there has been a decline in Covid-19 cases in Indonesia. So that the Elementary School in Boloagung Village has started holding face-to-face meetings. Children need to get adequate information and easy-to-understand health protocols when starting face-to-face school. This service is carried out directly in Boloagung Village. This activity is intended for grade 1 to grade 6 children and the socialization is done by coloring the picture media. The image media presented is in the form of a series of simple images containing concise messages and information. The result of this program is that participants understand more about health protocols that are carried out during face-to-face schools. Participants were very enthusiastic about participating in this program.